2012
DOI: 10.3147/jsfp.47.100
|View full text |Cite
|
Sign up to set email alerts
|

In situ Hybridization Detection of Koi Herpesvirus in Paraffin-embedded Tissues of Common Carp Cyprinus carpio Collected in 1998 in Korea

Abstract: 1-4). KHV i s t h e e t i o l o g i c a l a g e n t o f a n e me r g i n g a n d mo r t a l d i s e a s e i n c o mmo n c a r p a n d o r n a me n t a l (k o i) c a r p 5-7) 魚病研究 F i s h P a t h o l o g y , 4 7 (3) , 1 0 0-1 0 3 , 2 0 1 2. 9 © 2 0 1 2 T h e J a p a n e s e So c i e t y o f F i s h P a t h o l o g y * Co r r e s p o n d i n g a u t h o r E-ma i l : j wd o @n f r d i. g o. k r Fi g. 1. Sa mp l i n g s i t e s o f d i s e a s e d c o mmo n c

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Lee et al . () applied in situ hybridization (ISH) method to detect KHV DNA in paraffin‐embedded tissue specimens and suggested that the mass mortality of carp in 1998 in South Korea was associated with KHV infection and thus KHV was introduced into fish culture farms in South Korea in 1998 or earlier. Importation of koi from Asian countries to Iran has increased during the last decade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al . () applied in situ hybridization (ISH) method to detect KHV DNA in paraffin‐embedded tissue specimens and suggested that the mass mortality of carp in 1998 in South Korea was associated with KHV infection and thus KHV was introduced into fish culture farms in South Korea in 1998 or earlier. Importation of koi from Asian countries to Iran has increased during the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of an Asian genotype in Iran shows that importation of ornamental fish from Asian countries and shortcomings in diagnostic methods and lack of quarantine legislation to control and prevent of spread of this important new virus was the cause of mass mortality of koi, C. carpio in Iran. Lee et al (2012) applied in situ hybridization (ISH) method to detect KHV DNA in paraffin-embedded tissue specimens and suggested that the mass mortality of carp in 1998 in South Korea was associated with KHV infection and thus KHV was introduced into fish culture farms in South Korea in 1998 or earlier. Importation of koi from Asian countries to Iran has increased during the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…(v) Additionally, the virus has also been spread nationally and internationally before regulators were aware of the disease and methods to detect CyHV-3 were available. This is evidenced by the detection of CyHV-3 DNA in archive histological specimens collected during unexplained mass mortalities of koi and common carp in the UK in 1996 and in cultured common carp in South Korea in 1998 (Haenen et al, 2004;Lee, Jung, Park, & Do, 2012).…”
Section: Geographical Distribution and Prevalencementioning
confidence: 99%
“…IF and ISH methods, performed on separated fish leucocytes obtained by nondestructive (nonlethal) techniques, have also been used in research applications for detection or identification of CyHV-3 (Bergmann, Lutze, et al, 2010;Bergmann et al, 2009). ISH has also been applied to successfully detect CyHV-3 DNA in archive paraffin-embedded tissue specimens collected during unexplained mass mortalities of koi and common carp in the UK in 1996, and in cultured common carp in South Korea in 1998 (Haenen et al, 2004;Lee et al, 2012).…”
Section: Other Diagnostic Assaysmentioning
confidence: 99%
“…(Eide et al, 2011;El-Matbouli and Soliman, 2011;Fabian et al, 2013;Reed et al, 2014). The first outbreak of koi herpesvirus disease in East Asian and Southeast Asian can be traced back to 1998 in Korea (Lee et al, 2012), 2002 in Indonesia (Sunarto et al, 2005) and 2003 in Japan (Sano et al, 2004). The first detection of CyHV-3 from imported fish in China was reported in 2002 (Liu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%